PENGEMBANGAN MEDIA PEMBELAJARAN MODUL TEKNIK PEMESINAN CNC FRAIS BERBASIS E-PUBLICATION UNTUK SMK BERDASARKAN GAYA BELAJAR SISWA - Muchamad Yusuf Adi Rahmawan; Herman Saputro; Indah Widiastuti (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
In this modern era, almost every student has a smartphone. They use it everyday, not only for communication but also education purpose.  Technologies can be used in education by developing an instructional material based on a smartphone. The aims of this research to improve an e-publication module by identifying the student profile. MDLC (Multimedia Development Life Cycle) model is used. It consist of 6 stages: concept, design, collecting material, assembly, testing, and distribution. The student's profile was identified by using a learning style questionnaire and preference assessment. It consists of defining references, module frameworks, and storyboard. Encompasses system testing and testing by experts was taken. Professional teacher in education and instrument expert was invited and did assessment. They evaluated instructional material has made. The research showed the developed module is dominated in the form of text. Learning system media based e-publication compatible with low specs smartphone. Expert score reach 78.87%, it mean good instructional media. Teachers as the subject of this instructional media earned 96.4%. Its mean E-publication help students to learn better.